Removal of Aflatoxins Using Agro-Waste-Based Materials and Current Characterization Techniques Used for Biosorption Assessment - Vázquez-Durán, Alma; Nava-Ramírez, María de Jesús; Téllez-Isaías, Guillermo; Méndez-Albores, Abraham (Frontiers in Veterinary Science, 2022)
Aflatoxins are the most hazardous fungal-generated secondary metabolites produced by toxigenic Aspergillus species. These toxins are frequently detected in food and feed and impose either acute or chronic effects in humans and animals, causing great public concern. Because of the adverse effects of aflatoxins, many physical, chemical, and biological decontamination approaches have been developed. However, the most commonly used procedure is the addition of adsorbent materials into aflatoxin-contaminated diets to reduce toxin absorption and distribution to blood and target organs. In recent times, sorption technology with agro-waste-based materials has appeared as a promising alternative over conventional binding agents with the benefits of low cost, higher rentability, feasibility, and exceptional efficiencies. This review is mainly focused on discussing the most important agro-waste-based materials able to adsorb aflatoxins such as pomaces, seeds, stems, hulls, peels, leaves, berries, lignins, fibers, weeds, and various horticultural byproducts. Further data of the in vitro, in vivo, and in silico efficacy of these biomaterials to adsorb and then desorb aflatoxins are given. Besides, an overview of the main characterization techniques used to elucidate the most important physical and chemical mechanisms involved in the biosorption is presented. Finally, conclusions and future research necessities are also outlined.